Don Quijote und Rosenkreuz. Die Chymische Hochzeit als alchemokritischer Ritterroman - Carlos Gilly (Recherches Germaniques)
From an early time scholars have almost exclusively regarded Johann Valentin Andreae as a theologian, a critic of his times or even a Hermetist. As such they hardly noticed what a marvellous German writer, master of parody and great connoisseur of contemporary popular literature he was. Andreae read Cervantes’ novel Don Quixote (1605) in the original even before writing the Chymical Wedding in 1607. Years later, Andreae also erected a literary monument to its author in one of the dialogues in his Menippus (1617), by adopting and reworking the prologue to Don Quixote as the epitome of great literature. What is more, there is substantial evidence that –taking example of the Spanish model he had before him – Andreae also conceived of his Chymical Wedding as an ironic chivalric romance directed against the alchemists.